The Effectiveness of an E-Booklet in Enhancing Scientific Explanation Skills on the Human Immune System Topic - Rohmah, Siti Ainur; Nasution, Nanda Eska Anugrah; Khotimah, Khusnul (META: Journal of Science and Technological Education, 2025)
This study investigates the effectiveness of an e-booklet in improving students' scientific explanation skills in the human immune  system topic. A quasi-experimental design was employed, involving two groups: an experimental class using the e-booklet and a control class relying on conventional teaching methods. The study was conducted at SMAN 1 Leces Probolinggo, with 31 students in each group. Pretest and posttest assessments were used to measure scientific explanation skills, which were analyzed through statistical tests, including normality, homogeneity, t-test, and N-gain calculations. The results showed that the experimental class had a significantly higher improvement in scientific explanation skills than the control class. The N-gain score for the experimental class was 0.507, classified as moderate, whereas the control class scored 0.142, classified as low. The analysis of the three components of scientific explanation: claims, evidence, and reasoning indicated that the e-booklet was particularly effective in enhancing students' ability to construct claims and provide supporting evidence, while reasoning skills showed moderate improvement. Statistical analysis using the Mann-Whitney test confirmed a significant difference in posttest scores between the two groups (p<0.05), supporting the effectiveness of the e-booklet. The findings suggest that the e-booklet serves as an effective digital learning tool for fostering scientific explanation skills.